Persepsi Siswa Terhadap Implementasi Model Problem Based Learning pada Mata Pelajaran Matematika - Aprilita, Thesa Dwi; Handican, Rhomiy (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Problem-Based Learning (PBL) is a learning approach that emphasizes problem-solving through a real context. This study aims to examine perceptions of PBL implementation in the educational context and gain an understanding of its benefits and effectiveness. The research method used is descriptive quantitative which involves analyzing various studies that have been conducted previously. The research findings show that students' perceptions of PBL implementation are that PBL provides significant benefits for students, including increased concept understanding, learning motivation, problem-solving skills, critical thinking skills, and active engagement in the learning process. PBL also contributes to the development of collaboration, communication, and problem-solving skills in a real-life context. The results of this study provide a strong view that PBL implementation can be an effective alternative in enriching students' learning experiences and improving their learning outcomes. However, it requires a good approach to planning and implementing PBL, as well as adequate support from teachers, students, and educational institutions. In the context of modern education which is oriented towards skills and knowledge application, PBL is a relevant and important approach to prepare students to face real-world challenges. Further research is needed to better understand the implementation of PBL in various settings.